Do sensível ao inteligível: o Auto de São Lourenço - Costa, Paulo Eduardo da Silva (2007)
The theater was one of the most important pedagogical resources used by the Jesuit missionaries in the context of Catholic Reformation on 16th century. The playing of popular Autos , with religious connotation, brings the promotion of Catholic Faith between the natives of Portuguese America and their adaptation to Euro-Christian culture. The elaboration of cultural representations a process of meetings and confrontations, characteristic of the mercantile salvation effort, the formation of new models of social organization and values, in a scope of mestizo culture having new paradigms as basis, had some aspects of great relevance for an analysis of missionary action done by the Society of Jesus. This work analyses these aspects, through a document that was destined, in its origin, to promote the insertion of natives in Colonial society: the Auto de São Lourenço, written by priest José de Anchieta from 1580 to 1583. As a mestizo object , the Auto is a notable example of pedagogical resources used by Jesuits in native catechism. Crossing distinct traditions, José de Anchieta intending in accord with universal nature of his Order to do the Christianization of aboriginal cosmogony, in a baroque culture perspective. José de Anchieta produces, in this play, an intense signs interchange, where Art, Education and Religion are inseparable. Today, this type of cultural intermediation, as part of Jesuit s catechism, it´s a proficuous field of research and discussions on the historical culture.